Characterisation of plastic wads: A useful approach for elucidating shooting accidents and homicides involving shotguns. (March 2022) - Rotter, Gabriele; Correzzola, Claudio; Del Ángel, Vanessa Fossati; Daminato, Eva; Causin, Valerio
Highlights: wads are components of shotgun cartridges. wads are very under-investigated pieces of evidence. wads can be useful for identifying and comparing ammunition. a method is proposed to discriminate apparently similar commercial wads. the reconstruction of shooting incidents can be facilitated. Abstract: Wads are components of shotgun cartridges used for transferring to pellets or slugs the kinetic energy produced during the combustion chain which takes place as the trigger is pulled by the shooter. The hull of the cartridge falls in the vicinities of the gun, so it is easy for a malicious shooter to cancel this particular trace from a crime scene. However, the wad is projected to an intermediate point between the shooter and the victim, it is easily lost, and so it can be useful as a trace containing information on the type of ammunition used by a shooter and possibly a convenient item for comparison with analogous objects found in the premises of a suspect. In this paper, various analytical approaches, such as thermal analysis, infrared spectroscopy and X-ray diffraction were employed in order to discriminate apparently similar commercial wads. Samples that had previously been fired and pristine samples were examined, verifying that the energy, temperature and pressure associated to the combustion of the powder in the bore does not bring about appreciable changes in the polymer structure, thus allowing to use this approach in casework.